Parasitic Helminths and Zoonoses From Basic to Applied Research - Morales-Montor, Jorge; Hugo Del Río-Araiza, Victor; Hernandéz-Bello, Romel (IntechOpen, 2022)
This book provides updated information on helminth infections, with proposals for new treatments and biological factors of risk, the development of vaccines for the control of helminthiasis and explains the latest research on the field. It also delves into multi-omics, diagnosis, immunology, and novel molecule targets. In addition, the book examines topics such as host-parasite interaction. Key Features: • Provides basic and clinical evidence based on molecular interactions to address the risks and benefits of helminthiasis • Presents the results of new vaccine development • Discusses new and old therapeutic approaches in helminth infections • Delves into advances in the molecular and immune response in helminth infection • Proposes a One Health approach to study helminth infections • Analyzes the controversies and confusions in the management, biology, and control strategies of helminth infections • Examines the basic biology of helminth parasites